2011
DOI: 10.3109/0886022x.2011.577546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Cisplatin- and Oxaliplatin-Induced Oxidative Stress in Human Embryonic Kidney (HEK) 293 Cells

Abstract: Generation of reactive oxygen species (ROS) is involved in the nephrotoxicity of platinum anticancer drugs. This study involved incubation of human embryonic kidney (HEK) 293 cells in cell culture media supplemented with cisplatin or oxaliplatin in the presence or absence of curcumin, a well-studied antioxidant. Thereafter several indices of oxidative stress have been measured, which included glutathione (GSH), total antioxidant capacity (TAC), and antioxidant enzymes [(superoxide dismutase (SOD), catalase (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…Therefore, these concentrations were used to further elaborate the CP and DEP combined treatment in further experiments. Previous work from our research group reported that curcumin has antioxidant properties and protects against cytotoxicity in HEK-293 cells (Waly et al, 2011). Data presented in Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, these concentrations were used to further elaborate the CP and DEP combined treatment in further experiments. Previous work from our research group reported that curcumin has antioxidant properties and protects against cytotoxicity in HEK-293 cells (Waly et al, 2011). Data presented in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…(Waly et al, 2011(Waly et al, , 2012. However, the possible protective effect of curcumin on DEP, with or without CP, on HEK-293 toxicity has not been, as far as we are aware, investigated so far.…”
Section: Introductionmentioning
confidence: 87%
“…In an acute kidney injury model, oral administration of Curcumin (200 mg kg -1 per day for a week) significantly increased MDA concentration, nitric oxide and carbonylated proteins content in the rat kidney with bilateral renal ischemia, followed by reperfusion (Waly et al, 2011). On the other hand, Curcumin administration improved renal function on mice models (evaluated by blood urea nitrogen and albuminuria), which was associated with a decrease in inflammatory markers and matrix proteins (Trujullo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Curcumin administration improved renal function on mice models (evaluated by blood urea nitrogen and albuminuria), which was associated with a decrease in inflammatory markers and matrix proteins (Trujullo et al, 2013). Curcumin significantly improved oxidative stress by reducing TAC and GSH levels, as well as inhibiting the activity of CAT, GPX enzymes and SOD in human embryonic kidney cells (Waly et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1) is the main constituent of the spice turmeric (Curcuma longa) [7,33]. A number of studies have reported that curcumin has antidepressant, antioxidant, antihyperglycemic, antitumor, and anti-inflammatory activities [5,10,19,29,32]. However, the effect of curcumin on the production of TSLP has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%